THE IMPACT OF COVID-19 ON PHARMACY SERVICES AND PATIENT CARE - Mohammed Lafi Almutairi, Saleh Rshed Alrakaimi, Hamed Ramhan Almutairi, Salman Turki Alharbi; Abdulelah Saud Almutairi, Afnan Mohammed Abdullah Alharbi (Chelonian Research Foundation, 2024)
The emergence of the Covid-19 pandemic has significantly impacted healthcare systems worldwide, including pharmacy services and patient care. This essay explores the effects of Covid-19 on pharmacy services and other patient care services. Through a review of literature and analysis of data, this essay examines the changes in pharmacy services, medication management, patient interactions, and healthcare delivery due to the pandemic. The study highlights the challenges faced by pharmacies, the adoption of telehealth services, and the importance of implementing new strategies to ensure continued patient care during and post-pandemic. Keywords: Covid-19, pharmacy services, patient care, medication management, telehealth, healthcare delivery